2011
DOI: 10.1002/pits.20585
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the special issue: Resilience in schools

Abstract: This special issue, titled "Resilience in Schools," examines the theoretical and empirical bases of resilience in children and its implications for school practices that strengthen the success of children who are exposed to high-risk stressors or grow up under conditions of adversity. Each author uses a systemic approach to resilience that emphasizes the complex and integrated role of schools, families, and communities working together to foster students' educational and psychological wellbeing. Within this sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
11

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 0 publications
3
16
0
11
Order By: Relevance
“…As presented in Table 3, the mean academic achievement score for the low academic resilience category was 42.37 (SD=4.57), that for the moderate academic resilience category was 44.39 (SD=7.99) while that for the high academic resilience category was 58.66 (SD= 5.84). The pattern of the mean academic achievement scores was consistent with the results of previous studies that have reported a positive correlation between levels of academic resilience and levels of academic achievement (Esquivel, Doll, & Oades-Sese, 2011;Masten & Tellegen, 2012).…”
Section: Resultssupporting
confidence: 90%
“…As presented in Table 3, the mean academic achievement score for the low academic resilience category was 42.37 (SD=4.57), that for the moderate academic resilience category was 44.39 (SD=7.99) while that for the high academic resilience category was 58.66 (SD= 5.84). The pattern of the mean academic achievement scores was consistent with the results of previous studies that have reported a positive correlation between levels of academic resilience and levels of academic achievement (Esquivel, Doll, & Oades-Sese, 2011;Masten & Tellegen, 2012).…”
Section: Resultssupporting
confidence: 90%
“…Esquivel, Doll & Oades-Sese, 2011 ).Unique to this study, females' resilience was more facilitative of prospective achievement than were males with similar resilience scores, which equated to relatively poorer outcomes. The facilitative quality of females' resilience was illustrated through positive predictive relationships between respective academic outcomes and cluster groups which outperformed both of the male cluster counterparts.…”
Section: Psychological Resilience and Prospective Academic Achievementmentioning
confidence: 85%
“…Resilience has predicted academic attainment in high school students (Capella & Weinsten, 2001;Gonzalez & Padilla, 1997;Martin & Marsh, 2006;Nota, Soresi & Zimmerman, 2004) where the conceptual frameworks of academic resilience and academic buoyancy have been developed to identify factors which may protect against stress (Martin & Marsh, 2008. Personal attributes including relatedness, a sense of mastery and spirituality (Prince-Embury, 2011;Kim & Esquivel, 2011) and support from parents and teachers (Bryan, 2005;Mullis, Rathge & Mullis, 2003;Prince-Embury, 2008) have contributed to resilience being used to underpin mental health services and academic success in school settings (Esquivel, Doll & Oades-Sese, 2011, Doll, Jones, Osborn, Dooley & Turner, 2011. In contrast, resilience has been less prominent in HE; limited understanding may have reflected inadequate pedagogy and support, especially for new groups of students with distinctive needs beyond those of the stereotypical HE learner (Walker, Gleaves & Grey, 2006).…”
Section: Psychological Resiliencementioning
confidence: 99%
“…The resilience assets empower individuals to mould an environment they are in, which in turn form their developmental processes. This is a widely accepted ecological framework for understanding the internal and external resilience assets, the dynamic interactions between risk and protective factors (see Doll et al 2011;Esquivel et al 2011;Gordon & Song 1994;Von Soest et al 2010).…”
Section: Calling For the Academic Resilience Approachmentioning
confidence: 99%